Access to information and social control as an informational practice: conceptual convergences - Oliveira, Marcelo Fernandes de [UNESP]; Fujita, Mariangela Spotti Lopes [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2024)
The objective of this article is to demonstrate that the area of Information Science has been developing a new theoretical paradigm of a socioinformational scientific nature. In it, the subarea of information practice gains prominence. Because it has the potential to map how people search, use, and exchange information in order to understand daily events. And, from there, seek solutions to your individual and collective problems in the digital environment with consequences for the set of social relations. This theme attracts concepts of praxis from Marxist critical theory and praxeological knowledge from Bourdieusian sociology into the theoretical discussion. The discussion is carried out in the interconnection between the legal structure of access to information and public transparency and the possibility opened since then for the exercise of social control and advocacy of ideas as an informational practice to combat corruption in Brazil. The conclusion indicates that conceptual convergences are strong, but await the development of empirical studies of information practice that can prove their effectiveness.
Keywords: Information Science; access to information; social control; ideias advocacy; conceptual covergences